Amphiphilic Copolymers for Versatile, Facile, and In Situ Tunable Surface Biofunctionalization (Adv. Mater. 42/2021). Issue 42 (19th October 2021) - Ruland, André; Schenker, Saskia; Schirmer, Lucas; Friedrichs, Jens; Meinhardt, Andrea; Schwartz, Véronique B.; Kaiser, Nadine; Konradi, Rupert; MacDonald, William; Helmecke, Tina; Sikosana, Melissa K. L. N.; Valtin, Juliane; et al.
Abstract : Surface Biofunctionalization In article number 2102489, Carsten Werner, Uwe Freudenberg, and co‐workers introduce a set of PEGylated styrene maleic acid(anhydride) copolymers with systematically varied molecular architecture—"anchor polymers"—and demonstrate their potentialities for adsorptive surface biofunctionalization of bulk materials.